THE ASIAN POLICY OF THE USA AFTER 2021 AND THE ISLAMIC EMIRATE OF AFGHANISTAN RESTORATION - МІНГАЗУТДІНОВА, Галина (Київський національний університет імені Т. Шевченка, 2025)
B a c k g r o u n d . The relevance of the problem lies in the fact of the restoration of the Taliban regime after the withdrawal of American troopsfrom Afghanistan and the country's acquisition of an uncertain status in the international arena due to the non-recognition of this regime as legitimateby the majority of the global community. The purpose of the article is to consider the role of the Taliban as an element associated with Washington'sformation of its policy towards Asia and the protection of US national interests.M e t h o d s . To prepare the study, the historical method was used to work with the background of the situation surrounding the US Asian policy;in addition, the methods of analysis and synthesis were applied, as well as the deduction method which was used to identify problematic issues inthis policy.R e s u l t s . It was established that Afghanistan was a zone of US interests in Asia since the beginning of the 20th century and gained particularimportance during the "great game" against the USSR. After George W. Bush declared a "war on terror" at the beginning of the 21st century, the firstoverthrow of the Taliban regime, established in the 1990s, took place for the first time. After the withdrawal of American troops from Afghanistan in2021, the Taliban movement restored its power in the country in a short period of time. The US Congress has initiated a thorough audit of the 20-yearpresence of troops in Afghanistan to determine the reasons for such a rapid fall of the "democratic" Afghan government, as well as to review USforeign policy towards the region. Surely, an important factor influencing this policy is the restoration of the Taliban after 20 years of US troopsstationed in the country to maintain order and stability, and understanding the specifics of how this regime functions and what it seeks. The Talibanregime is a complex combination of religious fundamentalism and the political and economic interests of individual functionaries of the movement,which makes it even more unpredictable for any kind of international interaction. At the same time, in the course of developing further steps duringcreation of US policy towards the region as a whole, it is necessary to take into account not only the non-ambiguous factor of regional dynamics, butalso the activities and interests of Pakistan and China; therefore, shaping foreign policy measures in the region must consider bilateral relations withthese countries. To develop regional policy, attention should also be paid to the miscalculations associated with the demands made on Afghanistanat the beginning of the 21st century regarding the formation of an inclusive government, internal military training, etc. C o n c l u s i o n . It has been determined that an important component of the failure of US policy towards Afghanistan was a rather one-sidedapproach to setting criteria for building a stable state and military system in the country, which was based largely on "Western" ideas about themilitary hierarchy and the priorities of the state's domestic policy and how it should function. In addition, the lack of attention to local societal contextsand non-existence of clear long-term plan for Afghanistan have also had a destructive impact on the approach of American administrations andcontributed to the chaotic and rapid events unfolding in 2021. Therefore, taking into account these miscalculations and considering the interests ofregional players and relations with them, Washington needs to "work on mistakes" to develop a further course towards Asia as a whole.

В с т у п . Актуальність проблеми зумовлена реставрацією режиму "Талібан" після виведення американських військ з Афганістану та набуттям цієї країни невизначеного статусу на міжнародній арені у зв'язку з невизнанням більшістю світової спільноти цього режиму як легітимного. Метою статті є розгляд ролі Талібану як елементу, що пов'язаний із формуванням Вашингтоном своєї політики щодо Азії та захистом національних інтересів США. М е т о д и . Під час дослідження використано історичний метод для роботи з бекграундом ситуації навколо азійської політики США і застосовано методи аналізу та синтезу, а також метод дедукції для виокремлення проблемних питань у цій політиці. Р е з у л ь т а т и . Встановлено, що Афганістан являв собою зону інтересів США в Азії з початку ХХ ст. та набув особливої ваги за часів "великої гри" проти СРСР. Після оголошення Дж. В. Бушем "війни з тероризмом" на початку ХХІ ст. відбулося перше повалення режиму Талібану, встановленого в 1990-ті рр. уперше. Після виведення американських військ з Афганістану в 2021 р. рух Талібану відновив свою владу в країні за короткий проміжок часу. Конгрес США ініціював ретельний аудит 20-річної присутності військ в Афганістані для з'ясування причин настільки стрімкого падіння "демократичного" афганського уряду, а також з метою перегляду зовнішньої політики США щодо регіону. Звичайно, важливим фактором впливу на цю політику є реставрація Талібану після 20-річного розквартирування військ США в країні для підтримання порядку і стабільності та розуміння специфіки того, як цей режим працює і чого прагне. Режим Талібан являє собою складне поєднання релігійного фундаменталізму та політико-економічних інтересів окремих функціонерів руху, що додає йому непередбачуваності для зовнішньої взаємодії. У ході розробки подальших кроків розвитку політики США щодо регіону в цілому необхідно зважати не лише не такий неоднозначний фактор регіональної динаміки, а й на діяльність та інтереси Пакистану та Китаю і формувати комплекс зовнішньополітичних заходів в Азії з огляду на двосторонні відносини з цими країнами. Для розробки регіональної політики слід звернути увагу і на прорахунки, пов'язані з висуванням вимог до Афганістану на початку ХХІ ст. у питанні формування інклюзивного уряду, внутрішньої військової підготовки тощо. В и с н о в к и . Визначено, що важливим складником невдачі політики США щодо Афганістану став доволі однобокий підхід до виставлення критеріїв побудови стабільної державної та військової системи в країні, який ґрунтувався здебільшого на "західних" уявленнях про військову ієрархію та пріоритети внутрішньої політики держави й те, як вона має функціонувати. Крім того, приділення недостатньої уваги локальним суспільним контекстам та відсутність чіткого довгострокового плану щодо Афганістану також деструктивно позначилися на підході американських адміністрацій і вплинуло на хаотичність та стрімкість подій, що розгорнулися в 2021 р. Зважаючи на ці прорахунки та інтереси регіональних гравців і відносини з ними, Вашингтону необхідно здійснити "роботу над помилками" для напрацювання подальшого курсу щодо Азії в цілому.
АЗІЙСЬКА ПОЛІТИКА США ПІСЛЯ 2021 РОКУТА ВІДНОВЛЕННЯ ІСЛАМСЬКОГО ЕМІРАТУ АФГАНІСТАН
Keywords: The Taliban movement; The US foreign policy; regional competition; Islamic fundamentalism; military contingent; national interests; The Taliban movement; The US foreign policy; regional competition; Islamic fundamentalism; military contingent; national interests; рух "Талібан"; зовнішня політика США; регіональна конкуренція; ісламський фундаменталізм; військовий контингент; національні інтереси; рух "Талібан"; зовнішня політика США; регіональна конкуренція; ісламський фундаменталізм; військовий контингент; національні інтереси